Modern Diagnostics of the Impact of Cardiovascular Diseases on the Stomach - Makhmudovich, Abduraimov Bobirjon; Gʻayrat oʻgʻli, Norbekov Rakhimjon; Narzullayevna, Uzoqova Oyjamol (American Journal of Bioscience and Clinical Integrity, 2025)
As a result of the studies, no bleeding or adverse effects on the cardiovascular system (recurrent myocardial infarction, stroke, etc.) were observed during treatment with Controloc. The drug was well tolerated in almost all patients. Complications of erosive and ulcerative lesions of the gastrointestinal mucosa, such as bleeding, were absent in all patients.